(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the theoretical intricacies of comparative-segmental morphonology, focusing on its foundational principles and practical implications. Morphonology, as a subfield of linguistics, examines the interplay between morphological and phonological structures. By comparing segmental patterns across languages, this study identifies universal tendencies and language-specific phenomena, offering insights into morphological paradigms, segmental alternations, and their phonological underpinnings. The discussion is supported by theoretical models and cross-linguistic data. This article contributes to a deeper understanding of morphonological processes and their relevance to broader linguistic theory.